Evolution and stabilization of subnanometric metal species in confined space by in situ TEM - Liu, Lichen; Zakharov, Dmitri N.; Arenal, Raul; Concepcion, Patricia; Stach, Eric A.; Corma, Avelino (Nature communications, 2018)
Understanding the behavior and dynamic structural transformation of subnanometric metal species under reaction conditions will be helpful for understanding catalytic phenomena and for developing more efficient and stable catalysts based on single atoms and clusters. In this work, the evolution and stabilization of subnanometric Pt species confined in MCM-22 zeolite has been studied by in situ transmission electron microscopy (TEM). By correlating the results from in situ TEM studies and the results obtained in a continuous fix-bed reactor, it has been possible to delimitate the factors that control the dynamic agglomeration and redispersion behavior of metal species under reaction conditions. The dynamic reversible transformation between atomically dispersed Pt species and clusters/nanoparticles during CO oxidation at different temperatures has been elucidated. It has also been confirmed that subnanometric Pt clusters can be stabilized in MCM-22 crystallites during NO reduction with CO and H 2 . Understanding the behavior and structural transformation of metal species under reaction conditions is instrumental for developing more efficient and stable catalysts. Here, the authors reveal the evolution and stabilization of subnanometric Pt species confined in MCM-22 zeolite using in situ transmission electron microscopy.